Method for manufacturing laminated thin film, method for manufacturing solar cell, multi-junction solar cell, solar cell module and photovoltaic power generation system
By forming a p-electrode on the substrate of the solar cell and forming a cuprous oxide composite oxide film thereon, oxidation treatment under specific conditions, the problem of low conversion efficiency of cuprous oxide solar cells in the prior art is solved. Achieve efficient and low-cost solar cell manufacturing.
Patent Information
- Application Number
- CN202180019308.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-24
- Filing Date
- 2021-09-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-09-15
AI Technical Summary
In the prior art, when copper oxide (Cu2O) is used to manufacture solar cells, it is difficult to effectively improve the conversion efficiency of the battery and reduce costs.
A film containing mainly copper oxide and/or copper oxide composite oxide is formed on the substrate, followed by oxidation treatment, including the ozone partial pressure of 5 [Pa] or above and The treatment temperature is 273[K] or more and 323[K] or less, and the treatment time is 1 second or more and 60 minutes or less.
Through this method, the short circuit current and conversion efficiency of the solar cell are improved, the production cost is reduced, and the transparency and stability of the cell are enhanced.
Smart Images

Figure CN115398649B_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to a method for manufacturing a laminated thin film, a method for manufacturing a solar cell, a multi-junction solar cell, a solar cell module, and a photovoltaic power generation system. Background Art
[0002] A new type of solar cell uses cuprous oxide (Cu2O) as a light-absorbing layer. Cu2O is a wide-bandgap semiconductor. Since Cu2O is a safe and inexpensive material composed of copper and oxygen, which are abundant on Earth, it is expected to realize high-efficiency and low-cost solar cells.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: JP2018-46196A Summary of the invention
[0006] Problems to be solved by the invention
[0007] Embodiments of the present invention provide a method for manufacturing a stacked thin film through which a short circuit flows, a method for manufacturing a solar cell, a multi-junction solar cell, a solar cell module, and a photovoltaic power generation system.
[0008] Means for solving problems
[0009] The method for manufacturing a laminated thin film in an embodiment includes forming a p-electrode on a substrate; forming a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode; and performing an oxidation treatment on the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide. The ozone partial pressure in the oxidation treatment is 5 [Pa] or more and 200 [Pa] or less, the treatment temperature in the oxidation treatment is 273 [K] or more and 323 [K] or less, and the treatment time in the oxidation treatment is 1 second or more and 60 minutes or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a cross-sectional view of a solar cell according to an embodiment.
[0011] Figure 2 It is an explanatory diagram of analysis points of the solar cell according to the embodiment.
[0012] Figure 3 It is a flowchart of the manufacturing method of the laminated thin film and solar cell according to the embodiment.
[0013] Figure 4 is a cross-sectional view of a multi-junction solar cell according to an embodiment.
[0014] Figure 5 is a perspective view of a solar cell module according to an embodiment.
[0015] Figure 6 is a cross-sectional view of a solar cell module according to an embodiment.
[0016] Figure 7 is a structural diagram of a photovoltaic power generation system described in an implementation manner.
[0017] Figure 8 This is a conceptual diagram of a vehicle according to an embodiment.
[0018] Fig. 9 This is a concept drawing of a flying object.
[0019] Fig.10 is a table related to the embodiment.
[0020] Fig.11 is a table related to the embodiment. DETAILED DESCRIPTION
[0021] Hereinafter, embodiments will be described in detail with reference to the accompanying drawings. Unless otherwise specified, the values described in this specification are values at 25° C. and 1 atm (atmospheric pressure). The average value indicates the arithmetic mean.
[0022] (First Embodiment)
[0023] The first embodiment relates to a method for manufacturing a laminated film, a solar cell, and a method for manufacturing a solar cell. The laminated film is a component in the process of manufacturing a solar cell, and has a substrate, a p-electrode disposed on the substrate, and a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode. The surface of the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide is oxidized. Figure 1 is a cross-sectional view of the solar cell 100 according to the first embodiment. Figure 1 As shown, the solar cell 100 according to the present embodiment includes a substrate 1, a p-electrode 2 as a first electrode, a p-type light absorbing layer 3, an n-type layer 4, and an n-electrode 5 as a second electrode. An intermediate layer (not shown) may also be included between the n-type layer 4 and the n-electrode 5. Sunlight may be incident from the n-electrode 5 side or the p-electrode 2 side, but it is more preferably incident from the n-electrode 5 side. Since the solar cell 100 described in the present embodiment is a transmission type solar cell, the solar cell is preferably used in the top unit (light incident side) of a multi-junction solar cell. Figure 1 In the embodiment, the substrate 1 is disposed on the side of the p-electrode 2 opposite to the p-type light absorbing layer 3, but the substrate 1 may also be disposed on the side of the n-electrode 5 opposite to the n-type layer 4. Figure 1The mode shown in the figure is different, but a mode in which the substrate 1 is disposed on the n-electrode 5 side is also adopted except that the position of the substrate 1 is different. In the solar cell 100 described in this embodiment, light is incident from the n-electrode 5 side to the p-electrode 2 side.
[0024] The substrate 1 is a transparent substrate. The substrate 1 can be a transparent organic substrate such as acrylic, polyimide, polycarbonate, polyethylene terephthalate (PET), polypropylene (PP), fluororesin (polytetrafluoroethylene (PTFE), perfluoroethylene propylene copolymer (FEP), ethylene tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkane (PFA), etc.), polyarylate, polysulfone, polyethersulfone and polyetherimide, and an inorganic substrate such as soda-lime glass, white glass, chemically strengthened glass and quartz. As the substrate 1, the above substrates can be laminated.
[0025] The p-electrode 2 is disposed on the substrate 1 and between the substrate 1 and the p-type light absorbing layer 3. The p-electrode 2 is a transparent conductive layer disposed on the side of the p-type light absorbing layer 3. The thickness of the p-electrode 2 is generally greater than or equal to 100 nm and less than or equal to 2000 nm. Figure 1In the embodiment, the p-electrode 2 is in direct contact with the p-type light absorbing layer 3. The p-electrode 2 preferably includes one or more layers of transparent conductive oxide film (semiconductor conductive film). The transparent conductive oxide film is not particularly limited, and may be indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), gallium-doped zinc oxide (GZO), doped tin oxide, titanium-doped indium oxide (ITiO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), indium hydroxide-doped (IOH), etc. The transparent conductive oxide film may be a laminated film having a plurality of films. There is no particular limitation on the dopant used for oxide films such as tin oxide, as long as the dopant is one or more elements selected from In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. The p-electrode 2 preferably includes a tin oxide film doped with one or more elements selected from In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. The doped tin oxide film preferably contains less than 10 atomic % of one or more elements selected from In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. relative to the tin contained in the tin oxide film. As the p-electrode 2, a laminated thin film formed by laminating a transparent conductive oxide film and a metal film can be used. The thickness of the metal film is preferably less than 10 nm. The metal (including alloy) contained in the metal film is not particularly limited, and can be Mo, Au, Cu, Ag, Al, Ta, W, etc. The p-electrode 2 preferably includes a point-shaped, line-shaped or mesh-shaped electrode (selected from one or more of metals, alloys, graphene, conductive nitrides and conductive oxides) located between the transparent conductive oxide film and the substrate 1, or between the transparent conductive oxide film and the p-type light absorbing layer 3. The aperture ratio of the point-shaped, line-shaped or mesh-shaped metal relative to the transparent conductive film is preferably 50% or more. The point-shaped, line-shaped or mesh-shaped metal is not particularly limited, and can be Mo, Au, Cu, Ag, Al, Ta, W, etc. When the metal film is used for the p-electrode 2, the film thickness is preferably about 5 nm or less from the viewpoint of transparency. When a linear or mesh-shaped metal film is used, the film thickness of the metal film is not limited thereto because transparency is ensured through the openings.
[0026] Preferably, the p-electrode 2 has a stacked structure in which an indium tin oxide film and a doped tin oxide film are stacked on each other. Specifically, the p-electrode preferably has one or more stacked structures selected from a stacked film of an indium tin oxide film and an antimony-doped tin oxide film, a stacked film of an indium tin oxide film and a fluorine-doped tin oxide film, a stacked film of an indium tin oxide film and a tantalum-doped tin oxide film, and an indium tin oxide film and a niobium-doped tin oxide film. When the first transparent electrode 1 includes a doped tin oxide film, it is preferred that the doped tin oxide film is in direct contact with the p-type light absorbing layer 3.
[0027] The p-type light absorbing layer 3 is a p-type semiconductor layer. The p-type light absorbing layer 3 may be in direct contact with the p-electrode 2, or other layers may be present as long as the contact between the p-type light absorbing layer 3 and the p-electrode 2 can be ensured. The p-type light absorbing layer 3 is disposed between the p-electrode 2 and the n-type layer 4. The p-type light absorbing layer 3 is in direct contact with the n-type light absorbing layer 4. The p-type light absorbing layer 3 is a semiconductor layer of a metal oxide with copper as a main component. The metal oxide with copper as a main component is a composite oxide of cuprous oxide or / and cuprous oxide. That is to say, the p-type light absorbing layer 3 is a film mainly containing a composite oxide of cuprous oxide and / or cuprous oxide. The p-type light absorbing layer 3 is preferably a polycrystal of the composite oxide of cuprous oxide or / and cuprous oxide. The composite oxide of cuprous oxide or / and cuprous oxide is Cu a M1 b O c The oxide shown. M1 is preferably one or more elements selected from Sn, Sb, Ag, Li, Na, K, Cs, Rb, Al, In, Zn, Mg and Ca. a, b and c preferably satisfy 1.80≤a≤2.01 (a is greater than 1.80 and less than 2.01), 0.00≤b≤0.20 (b is greater than 0.00 and less than 0.20), 0.98≤c≤1.02 (c is greater than 0.98 and less than 1.02). Preferably, more than 90wt% of the p-type light absorption layer 3 is cuprous oxide and / or a composite oxide of cuprous oxide. More preferably, more than 95wt% of the p-type light absorption layer 3 is cuprous oxide or / and a composite oxide of cuprous oxide. It is further preferred that more than 98wt% of the p-type light absorption layer 3 is cuprous oxide and / or a composite oxide of cuprous oxide. Preferably, the p-type light absorbing layer 3 contains almost no heterogeneous phase of Cu and / or CuO. Since the transmittance of the p-type light absorbing layer 3 will increase, it is preferred that the p-type light absorbing layer 3 contains less heterogeneous phase and has good crystallinity. When the p-type light absorbing layer 3 contains the M2 element, the band gap of the p-type light absorbing layer 3 can be adjusted. The band gap of the p-type light absorbing layer 3 is preferably greater than 2.0 eV and less than 2.2 eV. When the band gap is within this range, sunlight can be effectively utilized in both the top unit and the bottom unit of the multi-junction solar cell, wherein a solar cell using Si in the light absorbing layer is used as the bottom unit, and the solar cell described in this embodiment is used as the top unit. The p-type light absorbing layer 3 preferably contains Sn and / or Sb. The Sn or Sb in the p-type light absorbing layer 3 can be Sn or Sb added to the light absorbing layer 3, or derived from the p-electrode 2.
[0028] The composition ratio of the p-type light absorbing layer 3 is the composition ratio of the entire p-type light absorbing layer 3. It is preferred that the compound composition ratio of the p-type light absorbing layer 3 is satisfied in the entire p-type light absorbing layer 3. When the concentration of Sn and Sb in the p-type light absorbing layer 3 is high, defects increase and carrier recombination increases. Therefore, the total volume concentration of Sb and Sn in the p-type light absorbing layer 3 is preferably 1.5×10 19 Atom / cm 3 the following.
[0029] When the thickness of the p-type light absorbing layer 3 is d3, the composition of the p-type light absorbing layer 3 is an average value of the compositions at depths of 0.2d3, 0.5d3, and 0.8d3 from the surface of the p-type light absorbing layer 3 on the side of the p-electrode 2. Unless there is a condition that the element composition ratio of the compound of the p-type light absorbing layer 3 is inclined, it is preferred that the p-type light absorbing layer 3 satisfies the above composition and the following appropriate composition at the above depth. In the analysis, for example, secondary ion mass spectrometry (SIMS) is used to analyze the composition at each distance from the surface of the n-type layer. Figure 2 The analysis points shown are analyzed at analysis points (A1 to A9) distributed as evenly as possible at equal intervals. Figure 2 It is a schematic diagram of the solar cell 100 observed from the light incident side. When analyzing the composition of the p-type light absorbing layer 3, D1 is the length of the p-type light absorbing layer 3 in the width direction, and D2 is the length of the p-type light absorbing layer 3 in the depth direction.
[0030] The thickness of the p-type light absorbing layer 3 is preferably 1,000 nm or more and 10,000 nm or less, as determined by cross-sectional observation with an electron microscope or by height measurement.
[0031] The p-type light absorbing layer 3 may contain elements such as Ga diffused from the n-type layer 4. Ga is not contained in the raw material for forming the p-type light absorbing layer 3, and Ga contained in the n-type layer 4 diffuses into the p-type light absorbing layer 3. When other elements are used to form the n-type layer 4, these elements may also diffuse into the p-type light absorbing layer 3.
[0032] The n-type layer 4 is an n-type semiconductor layer. The n-type layer 4 is disposed between the p-type light absorbing layer 3 and the n-electrode 5. The n-type layer 4 is in direct contact with the surface of the p-type light absorbing layer 3 on the opposite side of the surface in contact with the p-electrode 2. Preferably, the n-type layer 4 is a Ga-containing oxide semiconductor layer, and contains an oxide with Ga as a main component. In the n-type layer 4, the oxide with Ga as a main component may be mixed with other oxides, the oxide with Ga as a main component may be doped with other elements, or the oxide with Ga as a main component and doped with other elements may be mixed with other oxides. The n-type layer 4 is a single layer or a multilayer. Among the metal elements contained in the n-type layer 4, Ga is preferably more than 50 atomic %. The metal elements contained in the n-type layer 4 may be inclined from the p-type light absorbing layer 3 side to the n-electrode 5 side.
[0033] The n-type layer 4 preferably contains more than 90 wt % of an oxide containing M2 and Ga, wherein M2 is one or more elements selected from Al, B, In, Ti, Zn, Hf, Zr, Sn, Si and Ge.
[0034] Preferably, 90 wt% or more of the n-type layer 4 is an oxide containing M2 and Ga. More preferably, 95 wt% or more of the n-type layer 4 is an oxide containing M2 and Ga. More preferably, 98 wt% or more of the n-type layer 4 is a compound represented by an oxide containing M2 and Ga. Except for the intermediate region described below, the n-type layer 4 more preferably contains a compound represented by an oxide containing M2 and Ga.
[0035] Unless otherwise specified, the composition of the compound of the n-type layer 4 is the average composition of the entire n-type layer 4. When the thickness of the n-type layer 4 is d4, the composition of the n-type layer 4 is the average of the compositions at depths of 0.2d4, 0.5d4, and 0.8d4 from the surface of the n-type layer 4 on the side of the p-type light absorbing layer 3. Unless there is a condition that the element composition ratio of the compound of the n-type layer 4 is inclined, it is preferred that the n-type layer 4 satisfies the above composition and the following appropriate composition at the above depth. When the n-type layer 4 is very thin (for example, less than 5 nm), the composition at a depth of 0.5d from the surface of the n-type layer 4 on the side of the p-type light absorbing layer 3 can be regarded as the composition of the entire n-type layer 4. In the analysis, for example, secondary ion mass spectrometry (SIMS) is used to analyze the composition of the compound of the n-type layer 4 at each distance from the surface of the n-type layer 4. Figure 2 The analysis was performed at analysis points (A1 to A9) distributed as evenly as possible at equal intervals as shown in the analysis points. Figure 2 Schematic diagram of the solar cell 100 observed from the light incident side. When analyzing the composition of the n-type layer 4, D1 is the length of the n-type layer 4 in the width direction, and D2 is the length of the n-type layer 4 in the depth direction.
[0036] It is preferred that an intermediate region be included between the p-type light absorbing layer 3 and the n-type layer 4. The intermediate region is a transition region between the p-type light absorbing layer 3 and the n-type layer 4. The intermediate region includes a heterogeneous phase of cuprous oxide and a composite oxide of cuprous oxide of the p-type light absorbing layer 3 that becomes an interface defect. Examples of the heterogeneous phase included in the intermediate region include one or more phases selected from the group consisting of a CuO phase, a Cu phase, and Cu(OH)2. The intermediate region preferably includes a CuO phase.
[0037] The interface between the p-type light absorbing layer 3 and the n-type layer 4 may be unclear. When the interface between the p-type light absorbing layer 3 and the n-type layer 4 is unclear, the center portion of the unclear portion between the p-type light absorbing layer 3 and the n-type layer 4 is defined as the interface between the p-type light absorbing layer 3 and the n-type layer 4. The interface between the p-type light absorbing layer 3 and the n-type light absorbing layer 4 may be uneven and concave-convex. The interface between the p-type light absorbing layer 3 and the n-type layer 4 may be determined by observing the cross-section of the p-type light absorbing layer 3 and the n-type layer 4. Since the unclear portion between the p-type light absorbing layer 3 and the n-type layer 4 includes a non-homogeneous phase, the width of the unclear portion between the p-type light absorbing layer 3 and the n-type layer 4 in the stacking direction of the p-type light absorbing layer 3 and the n-type layer 4 is 0 nm or more and 10 nm or less, preferably 1 nm or more and 5 nm or less, and more preferably 2 nm or more and 4 nm or less.
[0038] The n-type layer 4 may contain an element such as Cu diffused from the p-type light absorbing layer 3. The raw material for forming the n-type layer 4 does not contain Cu, and Cu contained in the p-type light absorbing layer 3 diffuses into the n-type layer 4. When other elements are used when forming the p-type light absorbing layer 3, these elements may also diffuse into the n-type layer 4.
[0039] The n-electrode 5 is an electrode that is located on the side of the n-type layer 4 and has optical transparency to visible light. The n-type layer 4 is sandwiched between the n-electrode 5 and the p-type light absorbing layer 3. An intermediate layer (not shown) may be provided between the n-type layer 4 and the n-electrode 5. The intermediate layer may include a mesh or linear electrode. A transparent conductive oxide film (semiconductor conductive film) is preferably used for the n-electrode 5. The transparent conductive oxide film used for the n-electrode 5 is preferably one or more transparent conductive films selected from indium tin oxide, aluminum-doped zinc oxide, boron-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, titanium-doped indium oxide, indium gallium zinc oxide, and indium hydroxide-doped indium oxide. Graphene can also be used for the n-electrode 5. Graphene is preferably stacked with silver nanowires.
[0040] The thickness of the n-electrode 5 is obtained by cross-sectional observation with an electron microscope or by a height difference meter, and the thickness is not particularly limited, but is usually 1 nm or more and 2 μm or less.
[0041] For example, the p-type light absorbing layer 3 is preferably formed by sputtering. After the p-type light absorbing layer 3 is formed, the surface of the p-type light absorbing layer 3 is subjected to oxidation treatment.
[0042] Next, a method for manufacturing the laminated film and the solar cell 100 will be described. Figure 3 : is a flow chart of a method for manufacturing a solar cell 100 according to an embodiment. The method for manufacturing a solar cell 100 according to an embodiment includes the following steps: forming a p-electrode 2 on a substrate 1; forming a film of a composite oxide mainly containing cuprous oxide and / or cuprous oxide on the p-electrode 2; performing an oxidation treatment on the film of the composite oxide mainly containing cuprous oxide and / or cuprous oxide; forming an n-type layer 4 on the film of the composite oxide mainly containing cuprous oxide and / or cuprous oxide that has been subjected to oxidation treatment; and forming an n-electrode 5 on the n-type layer 4. The method for manufacturing a stacked thin film includes the following steps: forming a p-electrode 2 on a substrate 1; forming a film of a composite oxide mainly containing cuprous oxide and / or cuprous oxide on the p-electrode 2; and performing an oxidation treatment on the film of the composite oxide mainly containing cuprous oxide and / or cuprous oxide.
[0043] First, as a step of forming a p-electrode 2 on a substrate 1, a p-electrode 2 is formed on a substrate 1. A transparent conductive oxide film is formed, for example, by sputtering. When the p-electrode 2 includes a metal film, a mesh metal, or a linear metal, these metals are formed and patterned as needed.
[0044] Subsequently, as a step of forming a film mainly containing cuprous oxide and / or cuprous oxide composite oxide on the p-electrode 2, the film mainly containing cuprous oxide and / or cuprous oxide composite oxide is formed on the p-electrode 2 of the member having the p-electrode 2 formed on the substrate 1. The film mainly containing cuprous oxide and / or cuprous oxide composite oxide is preferably formed by sputtering. It is preferred to form a film mainly containing cuprous oxide and / or cuprous oxide composite oxide with less heterogeneous phase. Preferably, the member having the p-electrode 2 formed on the substrate 1 is heated to 300°C or more and 600°C or less, and sputtering is performed in the range of oxygen partial pressure of 0.01 [Pa] or more and 4.8 [Pa] or less and in the range of 0.02 μm / min or more and 20 μm / min or less. From the perspective of forming a polycrystalline film with high permeability and large grain size, when the deposition rate is d, it is more preferred that the oxygen partial pressure satisfies 0.55xd [Pa] or more and 1.00xd [Pa] or less. More preferably, the heating temperature is 350° C. or higher and 500° C. or lower. The M1 element may be added in the process of forming a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide.
[0045] As a step of performing an oxidation treatment on a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide, the oxidation treatment is performed on a member having a p-electrode 2 formed on a substrate 1 and a film mainly containing cuprous oxide and / or cuprous oxide formed on the p-electrode 2. The oxidation treatment is performed at a predetermined temperature in an atmosphere containing ozone. The oxidation treatment is performed to oxidize an extremely thin area on the surface of the film mainly containing cuprous oxide and / or cuprous oxide, for example, an area 5nm or shorter from the surface of the film. When the oxidation treatment is performed under high temperature conditions, the oxidation proceeds to the deep part of the film mainly containing cuprous oxide and / or cuprous oxide composite oxide, and excessive copper oxides and the like are generated inside the film. As a result, the transparency of the film and the conversion efficiency of the solar cell are reduced. The oxidation treatment includes treating a member having a p-electrode 2 formed on a substrate 1 and a film mainly containing cuprous oxide and / or cuprous oxide formed on the p-electrode 2 in an atmosphere containing ozone in a vacuum chamber. As can be seen from the above, the oxidized region is preferably 5 nm or less, more preferably 3 nm or less, from the exposed surface of the film mainly containing cuprous oxide and / or cuprous oxide composite oxide toward the depth of the film.
[0046] When an oxidation treatment is performed on a member formed with a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide, the cuprous oxide and / or the composite oxide of cuprous oxide on the surface of the film is partially oxidized and converted into a CuO phase, a Cu(OH)2 phase, etc. The presence of these heterogeneous phases can be confirmed by X-ray diffraction (XRD) or X-ray photoelectron spectroscopy (XPS).
[0047] Preferably, the member on which a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide is formed on the p-electrode 2 is stored before and after the oxidation treatment to avoid causing an unexpected oxidation reaction. After the oxidation treatment step of the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide, the member after the oxidation treatment is preferably stored in an atmosphere with an oxygen partial pressure of 50 [Pa] or less and 100° C. or less, more preferably 50° C. or less, or the n-type layer 4 is continuously formed. For example, before forming the n-type layer 4, the member subjected to the oxidation treatment may be stored in an air atmosphere at 30° C. or less for 1 hour, preferably 30 minutes or less. Before the oxidation treatment, the member may be stored in an atmosphere with an oxygen partial pressure of 50 [Pa] or less and 100° C. or less, more preferably 50° C. or less, or may be stored in an air atmosphere at 30° C. or less for 1 hour, preferably 30 minutes or less. In these storage atmospheres, ozone may be contained at a content of 0.1% or less relative to the oxygen partial pressure.
[0048] In the oxidation treatment, the member having a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide formed on the p-electrode 2 is placed on a stage in a vacuum chamber, and the pressure is reduced so that the total pressure becomes 2×10 -4 [Pa] or more and 1×10 -1 [Pa] or less. After the total pressure of the vacuum chamber is stabilized, ozone (O3) gas is introduced. Before the ozone gas is introduced, the temperature of the member having a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide formed on the p-electrode 2 is adjusted to the following temperature.
[0049] The atmosphere of the oxidation treatment contains ozone. In addition to ozone, the atmosphere of the oxidation treatment may also contain oxygen, carbon dioxide, argon, helium or nitrogen. Since the atmosphere of the oxidation treatment does not contain active gases other than ozone, oxygen and carbon dioxide, active gases other than ozone, oxygen and carbon dioxide are not introduced into the chamber where the oxidation treatment is performed. The term "does not contain" means zero or essentially zero. The total pressure in the vacuum chamber during the oxidation treatment is preferably less than 10000 [Pa], more preferably less than 5000 [Pa], and further preferably less than 1000 [Pa]. The lower limit of the total pressure in the vacuum chamber during the oxidation treatment is higher than the ozone partial pressure, for example, the lower limit is greater than 5 [Pa].
[0050] In the oxidation treatment, the ozone partial pressure is preferably greater than 5 [Pa] and less than 200 [Pa]. When the ozone partial pressure is too low, the treatment time becomes longer, the productivity becomes poor, or the oxidation reaction cannot be carried out. When the ozone partial pressure is too high, the oxidation reaction proceeds from the surface of cuprous oxide and / or the composite oxide of cuprous oxide to the deep part. Therefore, the ozone partial pressure in the oxidation treatment is preferably greater than 5 [Pa] and less than 100 [Pa], preferably greater than 7 [Pa] and less than 100 [Pa], and more preferably greater than 10 [Pa] and less than 50 [Pa]. The oxygen partial pressure and the ozone partial pressure are the values in the above-mentioned chamber.
[0051] In the oxidation treatment, the treatment temperature is preferably 273 [K] or more and 323 [K] or less (0°C or more and 50°C or less). When the treatment temperature is too low, the treatment time is too long, the productivity decreases, or the oxidation reaction cannot be performed. When the treatment temperature is too high, the oxidation reaction proceeds from the surface of the oxidized cuprous oxide and / or the oxidized cuprous oxide composite oxide to the deep part. Therefore, the treatment temperature in the oxidation treatment is further preferably 283 [K] or more and 308 [K] or less (10°C or more and 35°C or less). The treatment temperature is the temperature of the surface of the cuprous oxide and / or the cuprous oxide composite oxide. Since the oxidation reaction proceeds gently, the heat generated by the oxidation reaction is small. Therefore, the temperature of the surface of the cuprous oxide and / or the cuprous oxide composite oxide in the component having a film mainly containing cuprous oxide and / or the cuprous oxide composite oxide formed on the p-electrode 2 is substantially the same as the temperature of the component having a film mainly containing cuprous oxide and / or the cuprous oxide composite oxide formed on the p-electrode 2. The temperature of the member on which the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide is formed on the p-electrode 2 is the set temperature of the stage of the chamber for the oxidation treatment.
[0052] In the oxidation treatment, the treatment time is preferably more than 1 second (about 0.017 minutes) and less than 60 minutes. When the treatment time is too short, oxidation reaction cannot be performed. When the treatment time is too long, oxidation reaction is performed from the surface of the composite oxide of cuprous oxide and / or cuprous oxide to the deep part. Therefore, the treatment time in the oxidation treatment is more preferably more than 1 minute and less than 30 minutes, and more preferably more than 1 minute and less than 10 minutes.
[0053] When the ozone partial pressure in the oxidation treatment is high, the oxidation process can be easily controlled by lowering the treatment temperature or shortening the treatment time. When the oxidation treatment temperature is high, the oxidation process can be easily controlled by lowering the ozone partial pressure or shortening the treatment time.
[0054] When the ozone partial pressure in the oxidation treatment is low, the oxidation process can be easily controlled by increasing the treatment temperature or extending the treatment time. When the oxidation treatment temperature is low, the oxidation process can be easily controlled by increasing the ozone partial pressure or increasing the treatment time.
[0055] The oxidation treatment described in this embodiment is susceptible to the influence of ozone partial pressure, treatment temperature and treatment time. When the ozone partial pressure is high, the temperature is high or the treatment time is long, the oxidation reaction is promoted. The oxidation treatment is carried out in a manner that these three conditions meet the above ranges, so that an extremely thin area on the surface of the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide can be oxidized. In particular, the ozone partial pressure (P[Pa]), treatment temperature (Temp[K]) and treatment time (Time[minutes]) in the oxidation treatment preferably satisfy the following relationship. In the following relationship expressions, multiplication is represented by * (asterisk). It is preferred to satisfy the relationship of 1.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤50.0 (“240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))” is 1.0 or more and 50.0 or less)), and it is preferred to satisfy the relationship of 3.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤35.0 (“ 240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))” is 3.0 or more and 35.0 or less)), and more preferably satisfies the relationship of 5.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤20.0 (“240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))” is 5.0 or more and 20.0 or less)). By having the above relationship among these three conditions, an extremely thin area on the surface of a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide can be more appropriately oxidized.
[0056] In the oxidation treatment, it is preferred to irradiate the surface of cuprous oxide and / or cuprous oxide composite oxide with ultraviolet light having a wavelength of 100 nm to 400 nm. Irradiation with ultraviolet light can promote the oxidation reaction. The irradiation intensity of ultraviolet light is preferably 0.5 μW / cm 2 Above and 800μW / cm 2 Below, more preferably 10 μW / cm 2 Above and 500μW / cm 2When irradiated with ultraviolet rays, the ozone partial pressure (P [Pa]), treatment temperature (Temp [K]) and treatment time (Time [minutes]) in the oxidation treatment preferably satisfy the relationship of 1.0 ≤ 240 * (1-exp (-0.01 * P)) * exp (-4175 / 8.31 / Temp) * (1-exp (-2 * Time)) ≤ 30.0 ("240 * (1-exp (-0.01 * P)) * exp (-4175 / 8.31 / Temp) * (1-exp (-2 * Time))" is 1.0 or more and 30.0 or less), preferably 3.0 ≤ 240 * (1-exp (-0.01 * P)) * exp (-4175 / 8.31 / Temp) *(1-exp(-2*Time))≤20.0 ("240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))" is 3.0 or more and 20.0 or less), and more preferably satisfies 5.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤15.0 ("240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))" is 5.0 or more and 15.0 or less). When the surface is irradiated with ultraviolet rays, by forming such a relationship among these three conditions, an extremely thin area on the surface of a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide can be more appropriately oxidized.
[0057] As a step of forming an n-type layer on a film that has been subjected to oxidation treatment and mainly contains cuprous oxide and / or a composite oxide of cuprous oxide, an n-type layer 4 is formed on a film that mainly contains cuprous oxide and / or a composite oxide of cuprous oxide, for example, by an atomic deposition (ALD) method or a chemical vapor deposition (CVD) method.
[0058] As a step of forming an n-electrode on the n-type layer 4, the n-electrode 5 is formed on the n-type layer 4 by sputtering or the like. When an intermediate layer is provided between the n-type layer 4 and the n-electrode 5, the intermediate layer is formed before forming the n-electrode 5. Through the above steps, the solar cell 100 including the substrate 1, the p-electrode 2, the p-type light absorbing layer 3 whose surface is subjected to oxidation treatment and mainly contains cuprous oxide and / or a composite oxide of cuprous oxide, the n-type layer 4, and the n-electrode 5 can be manufactured.
[0059] (Second Embodiment)
[0060] A second embodiment relates to a multi-junction solar cell. Figure 4is a conceptual cross-sectional view of a multi-junction solar cell 200 according to a second embodiment. Figure 4 The multi-junction solar cell 200 in the embodiment includes the solar cell (first solar cell) 100 described in the first embodiment located on the light incident side and the second solar cell 201. The band gap of the photoelectric conversion layer of the second solar cell 201 is smaller than the band gap of the light absorption layer 3 of the multi-junction solar cell 200 according to the first embodiment. Incidentally, the multi-junction solar cell according to the present embodiment includes a solar cell in which three or more solar cells are connected.
[0061] The band gap of the p-type light absorbing layer 3 of the solar cell 100 according to the first embodiment is about 2.0 to 2.2 eV, and therefore, the band gap of the light absorbing layer of the second solar cell 201 is preferably 1.0 eV or more and 1.6 eV or less. Preferably, the light absorbing layer of the second solar cell 201 is selected from any one or more compound semiconductor layers of a CIGS-based compound semiconductor layer and a CdTe-based compound semiconductor layer having a high In content, crystalline silicon, and a perovskite compound.
[0062] (Third Embodiment)
[0063] The third embodiment relates to a solar cell module. Figure 5 is a perspective view of a solar cell module 300 according to a third embodiment. Figure 5 In the solar cell module 300 of the present invention, the first solar cell module 301 and the second solar cell module 302 are stacked on each other. The first solar cell module 301 is located on the light incident side and includes the solar cell 100 of the first embodiment. The second solar cell 201 is preferably used in the second solar cell module 302.
[0064] Figure 6 is a cross-sectional view of the solar cell module 300. Figure 6 , the structure of the first solar cell module 301 is shown in detail, but the structure of the second solar cell module 302 is not shown. In the second solar cell module 302, the structure of the solar cell module is appropriately selected according to the light absorbing layer of the solar cell to be used. Figure 6 The solar cell assembly 300 in the figure includes a plurality of subassemblies 303 surrounded by dotted lines, wherein a plurality of solar cells 100 are arranged in a horizontal direction and are electrically connected in series with each other through wiring 304, and the plurality of subassemblies 303 are electrically connected to each other in parallel or in series. Adjacent subassemblies are electrically connected by busbars 305.
[0065] In the adjacent solar cells 100, the n-electrode 5 on the upper side and the p-electrode 2 on the lower side are connected by the wiring 304. Both ends of the solar cell 100 in the submodule 303 are connected to the bus bar 305. The bus bar 305 is preferably configured to electrically connect the plurality of submodules 303 in parallel or in series and to adjust the output voltage with the second solar cell module 302. Incidentally, the connection system of the solar cell 100 shown in the first embodiment is an example. The solar cell module may be configured as other connection systems.
[0066] (Fourth Embodiment)
[0067] The fourth embodiment relates to a solar photovoltaic power generation system. The solar cell assembly 300 of the third embodiment can be used as a generator for generating electricity in the solar photovoltaic power generation system of the fourth embodiment. The solar photovoltaic power generation system according to this embodiment generates electricity using a solar cell assembly, and specifically, the solar photovoltaic power generation system includes a solar cell assembly for generating electricity, a unit for converting the generated electricity into electric power, and a power storage unit for storing the generated electricity or a load for consuming the generated electricity. Figure 7 This is a conceptual diagram of a solar photovoltaic power generation system 400 according to this embodiment. Figure 7 The solar photovoltaic power generation system shown includes a solar cell module 401 (300), a converter 402, a battery 403, and a load 404. Either the battery 403 or the load 404 may be omitted. The load 404 may be configured to utilize the electric energy stored in the battery 403. The converter 402 is a device including a circuit or device for performing power conversion such as voltage conversion or DC-AC conversion, such as a DC-DC converter, a DC-AC converter, an AC-AC converter, etc. The configuration of the converter 402 may be appropriately configured according to the voltage generated, the configuration of the battery 403, and the load 404.
[0068] The solar cells included in the solar cell assembly 300 generate electricity, and the electric energy is converted by the converter 402 and stored in the storage battery 403 or consumed by the load 404. Preferably, the solar cell assembly 401 is provided with a sunlight tracking drive device for making the solar cell assembly 401 continuously face the sun, or a concentrator for collecting sunlight, or an additional device for improving the power generation efficiency, etc.
[0069] The solar photovoltaic power generation system 400 is preferably used in real estate such as houses, commercial facilities, and factories, or movable assets such as vehicles, aircraft, and electronic equipment. By using the solar cell with good conversion efficiency according to this embodiment in the solar cell module 401, an increase in power generation can be expected.
[0070] As an application example of the solar photovoltaic power generation system 400 , a vehicle is described below. Figure 8 It is a conceptual configuration diagram of the vehicle 500 . Figure 8 The vehicle 500 in the embodiment includes a vehicle body 501, a solar cell module 502, a power converter 503, a battery 504, a motor 505, and a tire (wheel) 506. The power generated by the solar cell module 502 disposed on the upper portion of the vehicle body 501 is converted by the power converter 503 and is charged to the battery 504 or consumed by a load such as the motor 505. The tire (wheel) 506 is rotated by the motor 505 using the power provided by the solar cell module 502 or the battery 504, so that the vehicle 500 can be moved. The solar cell module 502 may not be a multi-junction type, and may be composed only of the first solar cell module including the solar cell 100 according to the first embodiment. In the case of using a transparent solar cell module 502, it is preferable to use the solar cell module 502 as a window for generating electricity on the side of the vehicle body 501 in addition to the upper portion of the vehicle body 501.
[0071] The following describes an aircraft (multi-rotor helicopter) as an example of using a solar photovoltaic power generation system 400. The aircraft uses a solar cell module 401. The aircraft of the seventh embodiment uses the battery module 401 of the fourth embodiment. Fig. 9 The schematic diagram of the flying object 600 (quadcopter) in briefly describes the structure of the flying object described in this embodiment. The flying object 600 includes a solar cell module 401, an aircraft frame 601, a motor 602, a rotor 603 and a control unit 604. The solar cell module 401, the motor 602, the rotor 603 and the control unit 604 are arranged in the aircraft frame 601. The control unit 604 converts the power output from the solar cell module 401 and adjusts its output. The control unit 604 may also include a battery that can store the power generated by the solar cell module 401. The motor 602 rotates the rotor 603 using the power output from the solar cell module 401. By using the flying object 600 with the solar cell module 401 of this embodiment configured as above, a flying object that can fly using more power can be obtained.
[0072] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples.
[0073] Example
[0074] (Example 1)
[0075] ITO (In:Sn=80:20, film thickness 20nm) and ATO (Sn:Sb=98:2, 150μm) were deposited on the upper surface of the glass substrate in contact with the glass as the p-electrode on the back side. A Cu2O light-absorbing layer was formed on the transparent p-electrode by heating to 500°C in an oxygen or argon atmosphere. Fig.10 The surface of the Cu2O light absorbing layer was partially oxidized under the conditions shown in the table. Then, 10 nm of Ga 2.0 O 3.0 Deposited as an n-type layer. An AZO transparent conductive film was deposited on the n-type layer as an n-electrode. A solar cell was obtained by forming a MgF2 film as an anti-reflection film. The short-circuit current (Jsc), open-circuit voltage (Voc), fill factor (FF), conversion efficiency and transmittance of the obtained solar cell were evaluated. In addition, Fig.10 The values of the evaluation formula [240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))] for the ozone partial pressure (P[Pa]), the treatment temperature (Temp[K]), and the treatment time (Time[minutes]) during the oxidation treatment are shown.
[0076] (Examples 2 to 30 and Comparative Examples 1 to 7)
[0077] In Examples 2 to 30, in addition to placing the solar cell in Fig.10 The solar cell was manufactured in the same manner as in Example 1 except that the oxidation was carried out under the conditions shown in the table. The short-circuit current (Jsc), open-circuit voltage (Voc), conversion efficiency and transparency of the obtained solar cell were evaluated. No oxidation treatment was performed in Comparative Example 2. Ultraviolet irradiation was performed in Examples 26 and 27. In Example 30, air was introduced to increase the total pressure.
[0078] (Example 31)
[0079] In addition to the 10nm Ga 0.8 Al 0.2 O 3.00 Deposited as an n-type layer, a solar cell was manufactured in the same manner as in Example 1. The obtained solar cell was evaluated for short-circuit current (Jsc), open-circuit voltage (Voc), conversion efficiency and transparency.
[0080] A solar simulator simulating an AM1.5G light source is used, and a Si cell is used as a reference under the light source to adjust the amount of light to 1 sun (1sun). The measurement is performed under normal pressure, and the temperature in the measurement chamber is 25°C. The voltage is scanned and the current density (current divided by the unit area) is measured. When the horizontal axis represents voltage and the vertical axis represents current density, the point intersecting the horizontal axis represents the open circuit voltage Voc, and the point intersecting the vertical axis represents the short circuit current density Jsc. On the measurement curve, when the voltage and current density are multiplied and the maximum value points are set to Vmpp and Jmpp (maximum power point), respectively, FF = (Vmpp*Jmpp) / (Voc*Jsc), and the conversion efficiency Eff. is obtained by Eff. = Voc*Jsc*FF.
[0081] exist Fig.11 In the table related to the embodiments, the short-circuit current (Jsc), open-circuit voltage (Voc), conversion efficiency and transmittance of the embodiments and comparative examples are comprehensively described.
[0082] When the transmittance in the band above 700nm and below 1200nm is 70% or more, the transmittance is evaluated as A; when the transmittance in the band above 700nm and below 1200nm is 60% or more and less than 70%, the transmittance is evaluated as B; when the transmittance in the band above 700nm and below 1200nm is less than 60%, the transmittance is evaluated as C.
[0083] When the conversion efficiency is 1.1 times or more of the conversion efficiency of Comparative Example 1, Jsc is evaluated as A; when the conversion efficiency is 1.0 times or more and less than 1.1 times the Jsc of Comparative Example 1, Jsc is evaluated as B; when the conversion efficiency is less than 1.0 times the Jsc of Comparative Example 1, Jsc is evaluated as C.
[0084] When Voc was 1.3 times or more of the conversion efficiency of Comparative Example 1, Voc was evaluated as A; when Voc was 1.1 times or more and less than 1.3 times the Voc of Comparative Example 1, Voc was evaluated as B; when Voc was less than 1.1 times the Voc of Comparative Example 1, Voc was evaluated as C.
[0085] When the conversion efficiency is 1.5 times or more of that of Comparative Example 1, the conversion efficiency is evaluated as A; when the conversion efficiency is 1.1 times or more and less than 1.5 times that of Comparative Example 1, the conversion efficiency is evaluated as B; when the conversion efficiency is less than 1.1 times that of Comparative Example 1, the conversion efficiency is evaluated as C.
[0086] from Fig.10 and Fig.11As can be seen from the table, by performing oxidation treatment under appropriate conditions, Jsc and the conversion efficiency of the solar cell are improved. By observing the surfaces after oxidation treatment of Example 1 and Comparative Example 1 by XRD, the peaks of the Cu2O phase, CuO phase and Cu(OH)2 phase in Example 1 can be confirmed. When no oxidation treatment is performed, the peak of the Cu2O phase can be confirmed, but the peaks of the CuO phase and Cu(OH)2 phase cannot be confirmed. In a multi-junction solar cell using the solar cell described in the embodiment as the top unit and a solar cell using Si for the light absorption layer as the bottom unit, its conversion efficiency is also improved.
[0087] In the specification, some elements are represented by only element symbols.
[0088] Next, description of the technical scheme of the implementation mode will be attached.
[0089] Technical Case 1
[0090] A method for manufacturing a laminated film comprises the following steps:
[0091] forming a p-electrode on the substrate;
[0092] forming a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode; and
[0093] performing an oxidation treatment on the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide,
[0094] The ozone partial pressure in the oxidation treatment is 5 [Pa] or more and 200 [Pa] or less.
[0095] The treatment temperature in the oxidation treatment is 273 [K] or more and 323 [K] or less, and
[0096] The treatment time in the oxidation treatment is 1 second or longer and 60 minutes or shorter.
[0097] Technical Case 2
[0098] According to the method for manufacturing a laminated thin film as described in Technical Solution 1,
[0099] The ozone partial pressure in the oxidation treatment is 7 [Pa] or more and 100 [Pa] or less.
[0100] The treatment temperature in the oxidation treatment is 283 [K] or more and 308 [K] or less, and
[0101] The treatment time in the oxidation treatment is 1 minute or more and 30 minutes or less.
[0102] Technical Case 3
[0103] According to the method for manufacturing a laminated thin film as described in Technical Solution 1,
[0104] The ozone partial pressure in the oxidation treatment is 10 [Pa] or more and 50 [Pa] or less.
[0105] The treatment temperature in the oxidation treatment is 283 [K] or more and 308 [K] or less, and
[0106] The treatment time in the oxidation treatment is 1 minute or more and 10 minutes or less.
[0107] Technical Case 4
[0108] The method for producing a laminated thin film according to any one of claims 1 to 3, wherein:
[0109] When the ozone partial pressure in the oxidation treatment is P[Pa], the temperature in the oxidation treatment is Temp[K], and the treatment time in the oxidation treatment is time[minutes], the relationship is satisfied:
[0110] 1.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤50.0.
[0111] Technical Case 5
[0112] The method for producing a laminated thin film according to any one of claims 1 to 4, wherein
[0113] The total pressure of the oxidation treatment is 10000 [Pa] or less.
[0114] Technical Case 6
[0115] According to the method for producing a laminated thin film according to any one of claims 1 to 5,
[0116] When the ozone partial pressure in the oxidation treatment is P[Pa], the treatment temperature of the oxidation treatment is Temp[K], and the treatment time of the oxidation treatment is time[minutes], the relationship is satisfied:
[0117] 3.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤35.0.
[0118] Technical Case 7
[0119] The method for producing a laminated thin film according to any one of claims 1 to 6, wherein:
[0120] In the oxidation treatment, the surface of cuprous oxide and / or cuprous oxide composite oxide is irradiated with ultraviolet light having a wavelength of 100 nm to 400 nm, and
[0121] The intensity of ultraviolet radiation is 0.5μW / cm 2 Above and 800μW / cm 2 the following.
[0122] Technical Case 8
[0123] The method for producing a laminated thin film according to any one of claims 1 to 7, wherein:
[0124] In the oxidation treatment, the surface of cuprous oxide and / or cuprous oxide composite oxide is irradiated with ultraviolet rays having a wavelength of 100 nm to 400 nm.
[0125] The intensity of ultraviolet radiation is 0.5μW / cm 2 Above and 800μW / cm 2 The following, and
[0126] When the oxygen partial pressure in the oxidation treatment is P[Pa], the treatment temperature in the oxidation treatment is Temp[K], and the treatment time in the oxidation treatment is time[minutes], the relationship is satisfied:
[0127] 1.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤50.0.
[0128] Technical Case 9
[0129] The method for producing a laminated thin film according to any one of claims 1 to 8, wherein:
[0130] In the oxidation treatment, the surface of cuprous oxide and / or cuprous oxide composite oxide is irradiated with ultraviolet rays having a wavelength of 100 nm to 400 nm.
[0131] The intensity of ultraviolet radiation is 0.5μW / cm 2 Above and 800μW / cm 2 The following, and
[0132] When the oxygen partial pressure in the oxidation treatment is P[Pa], the treatment temperature in the oxidation treatment is Temp[K], and the treatment time in the oxidation treatment is time[minutes], the relationship is satisfied:
[0133] 3.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤35.0.
[0134] Technical Case 10
[0135] The method for producing a laminated thin film according to any one of claims 1 to 9, wherein:
[0136] In the oxidation treatment, the surface of cuprous oxide and / or cuprous oxide composite oxide is irradiated with ultraviolet light having a wavelength of 100 nm or more and 400 nm or less.
[0137] The intensity of ultraviolet radiation is 0.5μW / cm 2 Above and 800μW / cm 2 The following, and
[0138] When the oxygen partial pressure in the oxidation treatment is P[Pa], the treatment temperature in the oxidation treatment is Temp[K], and the treatment time in the oxidation treatment is time[minutes], the relationship is satisfied:
[0139] 5.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤20.0.
[0140] Technical Case 11
[0141] The method for producing a laminated thin film according to any one of claims 1 to 10, wherein
[0142] The intensity of ultraviolet radiation is 10μW / cm 2 Above and 800μW / cm 2 the following.
[0143] Technical Case 12
[0144] The method for manufacturing a laminated thin film according to any one of technical solutions 1 to 11 further comprises:
[0145] An n-type layer is formed on the film which has been subjected to oxidation treatment and mainly contains cuprous oxide and / or a composite oxide of cuprous oxide.
[0146] Technical Case 13
[0147] The method for producing a laminated thin film according to any one of claims 1 to 12, wherein
[0148] The total pressure of the oxidation treatment is 5000 [Pa] or less.
[0149] Technical Case 14
[0150] The method for producing a laminated thin film according to any one of claims 1 to 13, wherein
[0151] The total pressure of the oxidation treatment is 1000 [Pa] or less.
[0152] Technical Case 15
[0153] A method for manufacturing a solar cell, comprising:
[0154] According to the method for manufacturing a stacked thin film as described in any one of technical solutions 1 to 14, the p-electrode is formed on a substrate;
[0155] The method for manufacturing a laminated thin film according to any one of claims 1 to 14, wherein the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide is formed on the p-electrode;
[0156] The method for producing a laminated thin film according to any one of claims 1 to 14, wherein an oxidation treatment is performed on the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode;
[0157] forming an n-type layer on the film which has been subjected to oxidation treatment and mainly contains cuprous oxide and / or a composite oxide of cuprous oxide; and
[0158] An n-electrode is formed on the n-type layer.
[0159] Technical Case 16
[0160] A multi-junction solar cell, comprising a solar cell manufactured according to the manufacturing method described in Technical Case 15.
[0161] Technical Case 17
[0162] A solar cell module, in which the solar cell manufactured according to the manufacturing method described in Technical Case 15 or the multi-junction solar cell described in Technical Case 16 is used.
[0163] Technical Case 18
[0164] A photovoltaic power generation system, in which the solar cell assembly described in Technical Case 17 is used to perform photovoltaic power generation.
[0165] Although certain embodiments have been described above, these embodiments are presented by way of example only and are not intended to limit the scope of the invention. Of course, the novel embodiments described herein may be embodied in various other forms; furthermore, various omissions, substitutions, and modifications may be made to the forms of the embodiments described herein without departing from the spirit of the invention. The appended claims and their equivalents are intended to cover forms or variations that fall within the scope and spirit of the invention.
[0166] Explanation of symbols
[0167] 100,101 Solar cell (first solar cell, top unit)
[0168] 1 Base
[0169] 2 p-electrode
[0170] 3 Light absorption layer
[0171] 4 n-type layer
[0172] 5 n-electrode
[0173] 200 multi-junction solar cells
[0174] 201 Second solar cell (bottom unit)
[0175] 300 Solar cell modules
[0176] 301 First Solar Cell Module
[0177] 302 Second solar cell module
[0178] 10 Base
[0179] 303 Subcomponents
[0180] 304 Wiring
[0181] 305 Busbar
[0182] 400 Solar Power Generation System
[0183] 401 Solar cell modules
[0184] 402 Converter
[0185] 403 Battery
[0186] 404 Payload
[0187] 500 vehicles
[0188] 501 Body
[0189] 502 Solar cell modules
[0190] 503 Power Converter
[0191] 504 Battery
[0192] 505 Motor
[0193] 506 Tire (Wheel)
[0194] 600 Flying Object
[0195] 601 Aircraft frame
[0196] 602 Motor
[0197] 603 Rotor
[0198] 604 Control Unit
Claims
1. A method for producing a laminated film, comprising the following steps: forming a p-electrode on the substrate; forming a film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode; and performing an oxidation treatment on the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide, The ozone partial pressure in the oxidation treatment is 5 [Pa] or more and 200 [Pa] or less, The treatment temperature in the oxidation treatment is 273 [K] or more and 323 [K] or less, and The treatment time in the oxidation treatment is 1 second or longer and 60 minutes or shorter.
2. The method for producing a laminated thin film according to claim 1, wherein: The ozone partial pressure in the oxidation treatment is 7 [Pa] or more and 100 [Pa] or less, The treatment temperature in the oxidation treatment is 283 [K] or more and 308 [K] or less, and The treatment time in the oxidation treatment is 1 minute or more and 30 minutes or less.
3. The method for producing a laminated thin film according to claim 1, wherein: The ozone partial pressure in the oxidation treatment is 10 [Pa] or more and 50 [Pa] or less, The treatment temperature in the oxidation treatment is 283 [K] or more and 308 [K] or less, and The treatment time in the oxidation treatment is 1 minute or more and 10 minutes or less.
4. The method for producing a laminated thin film according to any one of claims 1 to 3, wherein: When the ozone partial pressure in the oxidation treatment is set to P [Pa], the treatment temperature in the oxidation treatment is set to Temp [K], and the treatment time in the oxidation treatment is set to time [minutes], the following relationship is satisfied: 1.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤50.
0.
5. The method for producing a laminated thin film according to any one of claims 1 to 4, wherein: The total pressure of the oxidation treatment is 10000 [Pa] or less.
6. The method for producing a laminated thin film according to any one of claims 1 to 5, wherein: When the ozone partial pressure in the oxidation treatment is set to P [Pa], the treatment temperature of the oxidation treatment is set to Temp [K], and the treatment time of the oxidation treatment is set to time [minutes], the following relationship is satisfied: 3.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*Time))≤35.
0.
7. The method for producing a laminated thin film according to any one of claims 1 to 6, wherein: In the oxidation treatment, the surface of the cuprous oxide and / or the cuprous oxide composite oxide is irradiated with ultraviolet light having a wavelength of 100 nm to 400 nm, and The irradiation intensity of the ultraviolet light is 0.5 μW / cm 2 Above and 800μW / cm 2 the following.
8. The method for producing a laminated thin film according to any one of claims 1 to 7, wherein: In the oxidation treatment, the surface of the cuprous oxide and / or the cuprous oxide composite oxide is irradiated with ultraviolet rays having a wavelength of 100 nm to 400 nm. The irradiation intensity of the ultraviolet light is 0.5 μW / cm 2 Above and 800μW / cm 2 The following, and When the oxygen partial pressure in the oxidation treatment is set to P [Pa], the treatment temperature of the oxidation treatment is set to Temp [K], and the treatment time of the oxidation treatment is set to time [minutes], the following relationship is satisfied: 1.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤50.
0.
9. The method for producing a laminated thin film according to any one of claims 1 to 8, wherein: In the oxidation treatment, the surface of the cuprous oxide and / or the cuprous oxide composite oxide is irradiated with ultraviolet rays having a wavelength of 100 nm to 400 nm. The irradiation intensity of the ultraviolet light is 0.5 μW / cm 2 Above and 800μW / cm 2 The following, and When the oxygen partial pressure in the oxidation treatment is set to P [Pa], the treatment temperature of the oxidation treatment is set to Temp [K], and the treatment time of the oxidation treatment is set to time [minutes], the following relationship is satisfied: 3.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤35.
0.
10. The method for producing a laminated thin film according to any one of claims 1 to 9, wherein: In the oxidation treatment, the surface of the cuprous oxide and / or the cuprous oxide composite oxide is irradiated with ultraviolet rays having a wavelength of 100 nm or more and 400 nm or less, The irradiation intensity of the ultraviolet light is 0.5 μW / cm 2 Above and 800μW / cm 2 The following, and When the oxygen partial pressure in the oxidation treatment is set to P [Pa], the treatment temperature of the oxidation treatment is set to Temp [K], and the treatment time of the oxidation treatment is set to time [minutes], the following relationship is satisfied: 5.0≤240*(1-exp(-0.01*P))*exp(-4175 / 8.31 / Temp)*(1-exp(-2*time))≤20.
0.
11. The method for producing a laminated thin film according to any one of claims 7 to 10, wherein: The irradiation intensity of the ultraviolet light is 10 μW / cm 2 Above and 800μW / cm 2 the following.
12. The method for producing a laminated thin film according to any one of claims 1 to 11, wherein: Further comprising the steps of: An n-type layer is formed on the film mainly containing cuprous oxide and / or the composite oxide of cuprous oxide that has been subjected to the oxidation treatment.
13. The method for producing a laminated thin film according to any one of claims 1 to 12, wherein: The total pressure of the oxidation treatment is 5000 [Pa] or less.
14. The method for producing a laminated thin film according to any one of claims 1 to 13, wherein: The total pressure of the oxidation treatment is 1000 [Pa] or less.
15. A method for manufacturing a solar cell, comprising the following steps: The method for manufacturing a stacked thin film according to any one of claims 1 to 14, wherein the p-electrode is formed on the substrate; The method for producing a laminated thin film according to any one of claims 1 to 14, wherein the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide is formed on the p-electrode; The method for producing a laminated thin film according to any one of claims 1 to 14, wherein an oxidation treatment is performed on the film mainly containing cuprous oxide and / or a composite oxide of cuprous oxide on the p-electrode; forming an n-type layer on the film mainly containing cuprous oxide and / or cuprous oxide composite oxide subjected to the oxidation treatment; and An n-electrode is formed on the n-type layer.
16. A multi-junction solar cell, wherein: A solar cell manufactured according to the manufacturing method according to claim 15.
17. A solar cell module, wherein: A solar cell manufactured by the manufacturing method according to claim 15 or a multi-junction solar cell according to claim 16 is used.
18. A photovoltaic power generation system, wherein: Photovoltaic power generation is carried out using the solar cell assembly described in claim 17.
Citation Information
Patent Citations
Photoelectric conversion device and manufacturing method of photoelectric conversion device
JP2018046196A
Microelectronic structures including cuprous oxide semiconductors and having improved P-N heterojunctions
CN103189994A
Cuprous oxide-based multi-lamination heterojunction solar cell and preparation method thereof
CN105762219A